Towards sustainable global value chains in Asia and the Pacific - Masato Abe (International Journal of Small and Medium Enterprises and Business Sustainability, 2015)
This paper examines the present development of global value chains (GVCs), with particular attentions to the capacity building of small and medium-sized enterprises (SMEs) and the adoption of sustainable development agenda. The recent findings of both academic and policy literature on GVCs provide useful implications for both Governments and the business communities in Asia and the Pacific. The linkages between corporate and GVCs’ sustainability are explored, with special attention given to SMEs’ growing participation. More specifically, the paper highlights growth implications and challenges for SMEs in the context of specific industrial GVCs (agribusiness, garments and apparel, and automotive parts). The concepts of corporate social responsibility (CSR), circular economy, social investment and sustainability reporting are also examined in the context of relevance for and linkages with GVCs. Those analyses conclude with a number of policy options for national strategies and the design of economic policies to enhance the competitiveness of SMEs as well as the sustainability of GVCs.